Fishery characteristics of Portunid Crabs (Scylla serrata) from Two Different Sites Along the Sindh Coast (northern Arabian Sea) - Alam, Muhammad Rehan; Siddiqui, Pirzada Jamal; Hassan, Safia; Abbas, Ambareen; Akhtar, Saleem; Zafar, Mansoor; Somoro, Muhammad Hanif (Asian Journal of Biological and Life Sciences, 2018)
Portunid crab (Scylla serrata) is most abundant species and commonly known as mud crab. This study was conducted to estimate the sex ratio, carapace width (CW), body weight (BW) and maturity size from two different study sites along the Sindh Coast, Pakistan. A total of 253 and 272 individuals were collected from site 1 and site 2 respectively. The male and female represented sex ratio (1: 0.97) from site-1 and (1: 1.04) from site-2. The average catch per unit effort (CPUE) estimated during whole study period were (1.17±0.40) and (1.26±0.35) from site 1 and 2 respectively. The regression analysis for carapace width-weight indicated strong relationship and size frequency distribution representing higher abundance of individuals within the size class of CW (71-80), (81-90) and (91-110). This study would be helpful for management and monitoring local fishing practice to improve the catch and sustainability of wild population.
Keywords: Fisheries characteristics; Portunid crab; Scylla serrata